2007
DOI: 10.1002/mrd.20738
|View full text |Cite
|
Sign up to set email alerts
|

The GPI‐anchored CD52 antigen of the sperm surface interacts with semenogelin and participates in clot formation and liquefaction of human semen

Abstract: CD52 is a human glycosylphosphatidylinositol (GPI)-anchored antigen exclusively expressed in leukocytes and epididymal cells. It is also present in sperm, being inserted in their plasma membrane as they pass through the epididymis. In a previous paper we identified a new CD52 form without GPI anchor by fast performance liquid chromatography (FPLC) fractionation of semen components. The form has a lower negative charge than the GPI-anchored form and occurs as the only CD52 form in prostasome-free seminal plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This finding supports the hypothesis that asthenozoospermia is not caused by the presence of soluble Sgs in seminal plasma but by the presence of these Sgs in association with the spermatozoa. However, the molecular mechanism underlying the binding of SPMI to sperm is still unclear, and there are some factors that mediate SPMI binding to the sperm membrane, i.e., serine peptidase inhibitor-like molecules with Kunitz and WAP domains 1 (SPINLW1; eppin) [22] and CD52 (glycosylphosphatidylinositol; GPI-anchored antigen) [23] in humans. Moreover, SVS2, a protein that is homologous to Sgs in mice, selectively interacts with ganglioside GM1 on the sperm membrane to inhibit capacitation [24] .…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports the hypothesis that asthenozoospermia is not caused by the presence of soluble Sgs in seminal plasma but by the presence of these Sgs in association with the spermatozoa. However, the molecular mechanism underlying the binding of SPMI to sperm is still unclear, and there are some factors that mediate SPMI binding to the sperm membrane, i.e., serine peptidase inhibitor-like molecules with Kunitz and WAP domains 1 (SPINLW1; eppin) [22] and CD52 (glycosylphosphatidylinositol; GPI-anchored antigen) [23] in humans. Moreover, SVS2, a protein that is homologous to Sgs in mice, selectively interacts with ganglioside GM1 on the sperm membrane to inhibit capacitation [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Yang and colleagues have already demonstrated that these proteins are integral constituents of SF-EVs 25 . SEMG 1 has been found in complex with both the glycosylphosphatidylinositol (GPI)-anchored and soluble CD52, and it has been hypothesized that GPI-anchored CD52 serves as a dock for SEMG1 in anchoring the sperm cells to form clots 65 , later degraded by PSA to enable sperm motility. Recent studies found a negative correlation between sperm motility and the proportion of SEMGs bound spermatozoa 66,67 .…”
Section: Discussionmentioning
confidence: 99%
“…Another potential limitation of this research is that HCA could interfere with normal functions of CD52g, which are largely unknown. A report from Flori et al [60] provided evidence that CD52g anchors sperm to semenogelin in the semen clot that forms minutes after intercourse; it is unknown whether HCA affects this process. A final limitation is that the study was conducted in vitro, and a clinical trial will be required to determine the in vivo contraceptive efficacy of HCA.…”
Section: Discussionmentioning
confidence: 99%